Konsep Nilai dalam Peradaban Barat - Dinar Dewi Kania (Universitas Darussalam Gontor, 2013)
The Western’s conception of values, morals and ethics are so different with Islamic conception. In fact, there is difference about it between western scholars. These is a consequence from secularization that spread upon the whole Europe after their people’s believe of church’s conductiveness disappeared. This secularization impacts to the separation between religion’s doctrines and life activities as politic, education even to the marriage. In the end, Western society considers the values of religion are just subjective phenomenal that experienced by individual and are not universally. Religion has space its self that different with space of non-religion. The value and moral concept in West would be evolved and developed according to western society’s conception of human being reality, religion, sciences and life it’s self. This paper has a purpose to describes western scholar’s thoughts about values and moralities chronologically, starting from medieval centuries when Churches have the power of high legitimacy in western society until renaissance era and then describing about glorious era that the western scholar’s thoughts still influences the concept of values in this century.